Dariyāpāra - Ācārya, Guṇavantarāya (Gūrjara Grantharatna Kāryālaya, 2009)
Novel based on historical theme
Novel. - Reprint. Originally published: 1959. - In Gujarati-Schr
Keywords: Historical fiction; Gujarati